Partner Support Behavior Profile (PSBP) Ratings Among Non-Brain Injured Dyads - Wallin, Becky; Viau, Dana (My University, 2010)
This current project will validate the use of the Partner Support Behaviors Profile (PSBP) among non-brain injured individuals. The hypotheis is that untrained, non-brain injured dyads will have higher PSBP ratings, using fewer repair strategies, than untrained dyads consisting of individuals with traumatic brain injuries and their non-brain injured comunicative partners. The findings will establish a range of normal behaviors withing non-brain injured dyads to serve as comparative data for a dyad including an individual with a brain injury.
Color poster with text, table, and graphs.
Keywords: Couples--Communication; Caregivers--Communication; Brain damage--Patients--Communication; Brain damage--Patients--Family relationships; Caregivers--Family relationships; Posters